The Boston Type I Keratoprosthesis. Improving Outcomes and Expanding Indications - Aldave, Anthony J.; Kamal, Khairidzan M.; Vo, Rosalind C.; Yu, Fei (Elsevier BV, 2009)
Purpose: To report the usefulness of the Boston type I keratoprosthesis (Massachusetts Eye and Ear Infirmary, Boston, MA) in the management of corneal opacification, corneal limbal stem cell failure, or both in a large single-surgeon series. Design: Retrospective review of consecutive clinical case series. Participants: All patients undergoing keratoprosthesis implantation by a single surgeon (AJA) between May 1, 2004, and May 31, 2008. Methods: Data were collected regarding the preoperative characteristics of each eye undergoing keratoprosthesis implantation, the surgical procedure(s) performed, and the postoperative course. Statistical analysis was performed to identify factors influencing the incidence and severity of postoperative complications. Main Outcome Measures: Interval visual acuities, keratoprosthesis retention, and significant postoperative complications. Results: Fifty-seven keratoprosthesis procedures were performed in 50 eyes of 49 patients. The primary indication for surgery was repeat corneal transplantation failure (68%), although no prior corneal surgery had been performed in 16% of eyes. Preoperative visual acuity was 20/200 or worse in all eyes, with 88% of eyes having preoperative vision of counting fingers, hand movements, or light perception. The percentage of eyes with postoperative visual acuity of 20/100 or better was 67% at 6 months (n = 45), 75% at 1 year (n = 28), 69% at 2 years (n = 13), and 100% at 3 years (n = 7). In the 31% of patients in whom preoperative vision in the contralateral eye was 20/50 or better, the postoperative vision in the operative eye improved to 20/50 or better in 47% at the last follow-up (average, 18 months; range, 4-49 months). The overall keratoprosthesis retention rate was 84% at an average follow-up of 17 months (79 person-years of follow-up), with 100% retention in 8 eyes with no history of prior corneal transplantation (14.8 person-years of follow-up). The most common postoperative complications were retroprosthetic membrane formation (22 eyes) and persistent epithelial defects (19 eyes). No cases of infectious endophthalmitis were encountered, and only 1 patient with a history of glaucoma required additional glaucoma surgery during the postoperative period. Conclusions: The Boston type I keratoprosthesis is an effective means of managing repeat corneal graft failure and corneal limbal stem cell failure with or without corneal opacification in patients with both unilateral and bilateral visual impairment. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article. © 2009 American Academy of Ophthalmology.